A process for the directed catalytic conversion of higher phenols to lower phenols
Patent Information
- Application Number
- CN202610898186.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]中国专利201911345243.8公开了一种二甲酚催化加氢脱甲基反应用催化剂及其制备方法和应用,催化剂的组成包括复合载体、酸性活性组分,复合载体为改性 HY 分子筛和Al-MCM-41分子筛的复合物,改性的HY 分子筛外包覆有Al-MCM-41分子筛,形成的HY/MCM-41包覆型复合分子筛,在固定床反应器恒温段中装入催化剂,将体系压力恒定在1.0-3.5MPa、380-500℃,通入H2将催化剂还原活化3-6h,然后在320-450℃将二甲酚和水分别以相同的体积流量输送至反应器,进行二甲酚催化加氢脱甲基反应,最后得到苯酚和甲酚,3,4-二甲酚单程转化率可达到52.82%,其苯酚选择性和间对甲酚总的选择性依次为74.17%和22.32%,但在该申请中,原料需要采用纯度≥95%的高纯度的3,4-二甲酚,导致原料成本大幅度上升
[0030]一、工艺集成度高,降低投资成本
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application belongs to the field of coal chemical technology, specifically relating to a method for the directional catalytic conversion of higher phenols into lower phenols. Background Technology
[0002] Phenol is a key intermediate in the production of phenolic resins, pharmaceuticals, pesticides, and plastics, while cresol is an important raw material for synthetic resins, antioxidants, and fragrances. Both phenol and cresol have extremely high economic value. Currently, my country mainly relies on crude oil refining for phenol production, and although the production process is mature, it is greatly affected by fluctuations in international oil prices. Cresol production capacity is severely insufficient, and domestic market demand relies on imports for approximately 70%. In the low- and medium-temperature fractions (170-230℃) of coal tar, crude phenols account for over 50%. Low-boiling-point phenols such as phenol and cresol are easily separated and can be utilized through alkali washing and crude phenol refining. However, high-boiling-point, difficult-to-separate higher phenols, mainly ethylphenol and propionic acid, have lower economic value and require qualitative conversion into high-value phenol and cresol through dealkylation reactions.
[0003] Dealkylation of higher phenols can be achieved through both catalytic and non-catalytic processes. Non-catalytic processes primarily employ thermal cracking, achieving dealkylation through simple heating at 500°C; however, this method exhibits low conversion rates and low selectivity for the target product. Catalytic processes, on the other hand, can complete the dealkylation reaction at relatively lower temperatures, offering higher selectivity for the target product compared to non-catalytic processes; however, they suffer from engineering application problems such as catalyst deactivation and poor stability. Currently, widely used industrial catalysts for alkylphenol dealkylation mainly include molecular sieve materials and metal and metal oxide systems.
[0004] Chinese Patent 201911345243.8 discloses a catalyst for the catalytic hydrogenation and demethylation reaction of xylenol, its preparation method, and its application. The catalyst comprises a composite support and an acidic active component. The composite support is a composite of modified HY molecular sieve and Al-MCM-41 molecular sieve. The molecular sieve is coated with Al-MCM-41 molecular sieve to form a HY / MCM-41 coated composite molecular sieve. A catalyst is loaded into the isothermal section of a fixed-bed reactor, and the system pressure is kept constant at 1.0-3.5 MPa and 380-500℃. H2 is introduced to reduce and activate the catalyst for 3-6 hours. Then, xylenol and water are fed into the reactor at the same volumetric flow rate at 320-450℃ for catalytic hydrogenation and demethylation of xylenol, finally yielding phenol and cresol. The single-pass conversion rate of 3,4-xylenol can reach 52.82%, with phenol selectivity and total selectivity for m- and p-cresol at 74.17% and 22.32%, respectively. However, in this application, the raw material needs to be high-purity 3,4-xylenol with a purity ≥95%, leading to a significant increase in raw material costs.
[0005] Chinese Patent 201610397445.7 discloses a method for producing lower phenols from coal tar and the lower phenols obtained by this method. The method involves fractionating coal tar to obtain light distillate oil with a boiling range of less than 230℃ and heavy distillate oil with a boiling range of 230-500℃. The heavy distillate oil contains higher phenols. The heavy distillate oil is then used to extract phenols via alkaline washing, followed by hydrogenation in the presence of a hydrogenation catalyst to produce hydrogen-rich gas and liquid phase products. These liquid phase products are then fractionated to obtain phenolic oil containing lower phenols, from which the lower phenols are separated. This application involves hydrogenating the higher phenols in the coal tar, which reduces the selectivity of the lower phenols and decreases the utilization rate of the higher phenols.
[0006] In addition, severe carbon deposition on the catalyst during the reaction reduces its lifespan. Therefore, how to fully utilize alkylphenols in coal tar to produce lower phenols and improve catalyst lifespan remains a problem in the field of lower phenol production. Summary of the Invention
[0007] To at least partially achieve the following objectives—to fully utilize higher phenols in coal tar to produce lower phenols, especially cresol, and to reduce the rate of catalyst carbonization and improve catalyst lifespan—this application proposes a method for the directed catalytic conversion of higher phenols into lower phenols. This method employs a fixed-bed reactor, using higher phenols extracted from medium- and low-temperature coal tar as raw materials in the presence of a catalyst, and under a hydrogen atmosphere, simultaneously undergoing dealkylation and alkyl transfer reactions to produce phenol and cresol. After the reaction, the products are separated, separating the target product from the unreacted raw materials, with the unreacted raw materials returned to the reactor for recycling. The target product is the desired lower phenol. In this application, the lower phenol is phenol and / or cresol, and the higher phenols specifically include xylenol, tricresol, C2 and above alkylphenols, polyphenols, naphthol, etc. C2 and above alkylphenols can specifically be ethylphenol, propionic acid, and butylphenol. In this application, both higher and lower phenols are alkylphenols.
[0008] Currently, the preparation of lower phenols such as phenol and cresol using dealkylation and alkyl transfer methods involves two steps: first, converting heavy alkylphenols in the alkylphenol stream into phenols and alkenes; second, reacting unconverted methylphenols and phenols in the alkyl transfer process to generate cresol. Due to the large amount of olefins produced, the selectivity for cresol is low. This application utilizes a specially designed catalyst to simultaneously carry out dealkylation and alkyl transfer in the same fixed-bed reactor, generating both phenol and cresol. This allows for the processing of both single components and mixed phenols, maximizing resource utilization.
[0009] Furthermore, to increase the proportion of cresol in the product, the raw material also includes an alkyl transfer agent, which is any one of benzene, toluene, and phenol. Phenol is preferably used as the alkyl transfer agent, and when phenol is used as the alkyl transfer agent, the mass ratio of phenol to higher phenols is (0.5-1):1.
[0010] Phenol is a preferred alkyl transfer reagent. Adding phenol to the reaction system can efficiently accept the methyl groups removed from higher phenols (such as xylenol and tricresol) during dealkylation reactions, thereby generating cresol. Its advantages are: on the one hand, it suppresses the side reaction pathway of disproportionation reactions of alkylphenols such as xylenol to generate phenol; on the other hand, by using phenol as a methyl acceptor, the removed methyl group is converted into high-value cresol, thus significantly improving the overall selectivity of cresol.
[0011] Specifically, the reaction conditions are: reaction temperature 300-500℃, reaction pressure 0.1-5.0 MPa, and weight hourly space velocity (WHSV) 0.5-5.0 h⁻¹. -1 Hydrogen-to-oil volume ratio (200-1000):1.
[0012] Specifically, the catalyst is an acid-metal bifunctional synergistic catalyst, and its preparation method includes the following steps:
[0013] (1) Using mesoporous insertion technology, a hierarchical pore molecular sieve with a micro-mesoporous hierarchical pore structure was prepared;
[0014] (2) Modify the hierarchical pore molecular sieve by using P or B elements to obtain modified molecular sieve;
[0015] (3) The catalyst support is obtained by mixing, bonding, extruding and calcining the modified molecular sieve with a binder;
[0016] (4) An active metal component is loaded onto a catalyst support to obtain a catalyst; the active metal component is at least one of Ni, Mo, and W. Specifically, in step (3), the binder is at least one of boehmite or silica sol. Preferably, two or three active metal components are used simultaneously.
[0017] Specifically, the hierarchical molecular sieve has a multi-level pore structure including micropores, mesopores and macropores. By volume percentage, micropores account for 8-30% of the total pore volume, mesopores account for 50-83% of the total pore volume, and macropores account for 9-24% of the total pore volume.
[0018] Mesopore insertion technology mainly includes post-processing and template methods. Post-processing methods (such as alkaline etching) selectively dissolve silicon atoms on the finished microporous molecular sieve to "excavate" mesopores, which is simple and low-cost. Template methods introduce mesoporous agents (surfactants or carbon particles, etc.) in the early stage of synthesis, allowing the molecular sieve to grow around them. After crystallization, the mesoporous agent is removed, leaving regular mesopores with strong controllability of pore structure.
[0019] This application constructs hierarchical channels by inserting mesoporous material into molecular sieves and precisely adjusts the Bronsted and Lewis acid strength and distribution of the molecular sieves using P and B ions. Transition metals such as Ni, Mo, and W are loaded to provide hydrogenation / dehydrogenation activity, forming an acid-metal bifunctional synergistic system. This catalyst does not use polluting metals such as cadmium and is used to qualitatively catalyze the conversion of higher phenols extracted from medium- and low-temperature coal tar into lower phenols. Byproducts include low-aromatic hydrocarbons and other economically valuable products. This improves upon the problem of catalysts easily deactivating due to carbon buildup and requiring frequent regeneration when processing heavy feedstocks.
[0020] Specifically, in step (1), the hierarchical porous molecular sieve is obtained by desiliconizing a molecular sieve through alkali treatment, or it is a molecular sieve made using a mesoporous agent. When preparing a molecular sieve using a mesoporous agent, the mesoporous agent is added to the reactor before crystallization. In the specific preparation of molecular sieves, the mesoporous agent can be added together with raw materials such as silicon source and aluminum source, or it can be added to the precursor solution before the molecular sieve precursor is formed and crystallized. After crystallization is completed, the mesoporous agent needs to be removed in the subsequent calcination.
[0021] Specifically, the mesoporous agent is a mesoporous carbon material, carbon nanotubes, or polymer microspheres with a mesoporous structure. When carbon nanotubes are used as the mesoporous agent, the size of the carbon nanotubes is 1-20 nm.
[0022] Specifically, the hierarchical porous molecular sieve is any one or a mixture of at least two of Hβ, HZSM-5, HMCM-22, HMOR, HMCM-36, or HZSM-48. Preferably, two or more molecular sieves are mixed and used together to accommodate alkylphenols with different carbon numbers. The different pore sizes within the different molecular sieves accommodate alkylphenols with varying carbon numbers, thereby improving the efficiency of dealkylation and alkyl transfer reactions of alkylphenols. The silica-to-alumina ratio of the hierarchical porous molecular sieve is controlled between 20 and 100.
[0023] Specifically, in step (2), P or B elements are loaded onto a hierarchical porous molecular sieve using an impregnation method or chemical vapor deposition method. Based on the dry basis mass of the modified molecular sieve, the loading amount of P and B elements on the molecular sieve is 1-5 wt%, where P element is calculated as P2O5 and B element as B2O3. In actual production, the loading of P or B elements can be selected according to existing equipment and processes.
[0024] Specifically, the active metal component in the catalyst, calculated as an oxide, is 1-20% by mass. Preferably, the active metal component is 1-10% by mass, and more preferably 2-5%.
[0025] Specifically, in step (2), during the modification treatment, P or B is loaded onto the hierarchical pore molecular sieve by equal volume impregnation or ion exchange, and then the hierarchical pore molecular sieve is calcined at 500-600℃ for 3-4 to form a modified molecular sieve.
[0026] In step (3), the roasting temperature is 500-560℃ and the roasting time is 3-4h.
[0027] In step (4), the active metal component is loaded using an equal-volume impregnation method or an ion exchange method. After loading is completed, it is calcined at 500-560℃ for 3-4 hours.
[0028] The calcination temperature in each step should be basically consistent with the conventional calcination temperature of molecular sieves to avoid overheating and collapse of the molecular sieve structure due to excessively high temperatures. A suitable calcination time ensures the smooth formation of molecular sieve channels. If the calcination time is too long, some micropores will close, reducing the number of micropores; if the calcination time is too short, the unit cells cannot shrink sufficiently, making it difficult to form a stable framework structure.
[0029] Overall, this application has the following advantages:
[0030] I. High degree of process integration, reducing investment costs
[0031] Existing technologies separate dealkylation and alkyl transfer into two independent unit operations, requiring two reaction units and intermediate storage and transportation systems, resulting in a long process and high investment. This application couples the two reactions within a single fixed-bed reactor, reducing equipment investment by more than 30%; it also simplifies the process and reduces energy consumption and labor costs. Unreacted feedstock is recycled, and the overall conversion rate can reach over 92%, which is 10 percentage points higher than the stepwise process.
[0032] II. Constructing hierarchical channels within molecular sieves to extend catalyst lifetime.
[0033] Conventional microporous molecular sieves have narrow pores, restricting the diffusion of higher phenolic macromolecules and easily leading to carbon deposition and deactivation. This application introduces mesopores using alkali treatment or a hard template method, forming a micro-mesoporous hierarchical structure. Mesopores act as "highways," shortening the diffusion path and increasing the effective diffusion coefficient by 1-2 orders of magnitude; simultaneously, mesopores can accommodate carbon precursors, delaying pore blockage. Experiments show that the catalyst constructed with mesopores experiences an activity decrease of less than 8% after 400 hours of continuous operation, while the unmodified catalyst experiences a 25% activity decrease after 200 hours, with a 40% reduction in regeneration frequency.
[0034] III. Precisely modulate the acidity of molecular sieves to improve the selectivity of target products.
[0035] Existing molecular sieve catalysts suffer from difficulty in controlling acid distribution, product limitations due to thermodynamic equilibrium, and low cresol selectivity. This application employs P and B elemental modification of molecular sieves to modulate Brønsted / Lewis acids, achieving a more rational acid distribution through P+B synergy. Optimization of acid centers makes the reaction pathway more inclined to generate cresol, breaking the equilibrium limitation.
[0036] IV. Acid-metal synergy to suppress coking side reactions
[0037] Simple acid-catalyzed dealkylation produces a large amount of olefins, which are prone to polymerization and coking. This application simultaneously loads transition metals such as Ni, Mo, and W onto a molecular sieve, forming an acid-metal bifunctional system. The olefins generated from dealkylation are in-situ hydrogenated to alkanes at the metal sites, avoiding accumulation and polymerization at acidic sites. The reaction byproducts are mainly low-aromatic hydrocarbons and light alkanes, both high-value products that can be separated and used. Experimental verification shows that, compared with existing molecular sieve catalysts, the catalyst in this application can effectively reduce the byproduct olefins and heavy components, indicating that acid-metal synergy can effectively inhibit catalyst coking.
[0038] V. Raw material allocation, overcoming balance limitations
[0039] This application uses phenol as an alkyl transfer agent by mixing it in a specific ratio with higher phenols, and utilizes Le Chatelier's principle to shift the alkyl transfer equilibrium towards the formation of cresol. The reaction of phenol with polyalkylphenols can produce two cresols, further increasing the cresol yield.
[0040] VI. Environmentally friendly and with significant economic benefits
[0041] The catalyst does not contain polluting metals such as cadmium; the byproducts, low in aromatics, can be sold directly without waste discharge.
[0042] In summary, this application, through catalyst design and process coupling, outperforms existing technologies in terms of conversion rate, selectivity, stability, and economy. Detailed Implementation
[0043] In the following examples and comparative examples, obtaining cresol is the primary objective and obtaining phenol is the secondary objective. That is, the target products are cresol and phenol, but cresol is the primary target product and phenol is the secondary objective. Therefore, the goal is to maximize the selectivity of cresol.
[0044] Example 1
[0045] I. Preparation of Catalyst #1:
[0046] (1) Commercially available HZSM-5 molecular sieve (silicon-to-aluminum ratio 50) was treated with 0.2 mol / L NaOH solution at 65℃ for 2 h to remove silicon, and then washed with distilled water until neutral to introduce a mesoporous structure, thus obtaining a hierarchical channel molecular sieve with a micro-mesoporous hierarchical pore structure. The silicon-to-aluminum ratio of the hierarchical channel molecular sieve was 32.
[0047] (2) A phosphoric acid aqueous solution was used as the impregnation solution to impregnate the hierarchical porous molecular sieve with an equal volume, introducing 2 wt% phosphorus (P) element into the hierarchical porous molecular sieve, where P is calculated as P₂O₅. The hierarchical porous molecular sieve with introduced P element was dried at 100°C for 5 h, and then calcined at 550°C for 4 h to obtain the modified molecular sieve. In this application, the ratio of P element to B element is based on the dry basis mass of the modified molecular sieve, and will not be repeated in the subsequent examples and comparative examples.
[0048] (3) Using boehmite with an alumina content of 70wt% as a binder, the binder is mixed evenly with the modified molecular sieve, extruded into strips, dried at 100℃ for 5h, and then calcined at 520℃ for 4h to obtain the catalyst support.
[0049] (4) Using a mixed aqueous solution of nickel nitrate and ammonium heptamolybdate, Ni and Mo elements were loaded onto the catalyst support by an equal volume impregnation method. The catalyst support loaded with Ni and Mo elements was then dried at 100°C for 5 hours and then calcined at 500°C for 4 hours to obtain catalyst #1.
[0050] In catalyst #1, the mass percentage of binder (alumina) is 20%, the mass percentage of NiO is 2%, and the mass percentage of MoO3 is 1%.
[0051] II. Preparation of lower phenols:
[0052] Using C8 and higher alkylphenols extracted from medium- and low-temperature coal tar as raw materials (containing 35 wt% xylenol, 28 wt% tricresol, 20 wt% ethylphenol, with the remainder being propylphenol and a small amount of polyalkylphenols), phenol and higher phenols were fed in a 1:1 mass ratio, with phenol acting as an alkyl transfer agent. A fixed-bed reactor was loaded with catalyst #1, and under a hydrogen atmosphere, dealkylation and alkyl transfer reactions were carried out simultaneously to produce phenol and cresol. The reaction products were separated, with cresol and byproducts collected separately, and unreacted raw materials returned to the reactor for recycling. The reaction products were condensed and separated, and gas and liquid phases were collected for chromatographic analysis. The higher phenols identified were the C8 and higher alkylphenols extracted from medium- and low-temperature coal tar.
[0053] Reaction conditions: reaction temperature 450℃, reaction pressure 3.0 MPa, weight hourly space velocity 1.0 h⁻¹ -1 The hydrogen-to-oil volume ratio is 500:1.
[0054] The results showed that the single-pass conversion rate of higher phenols was 55.8%, the total conversion rate (including recycling) was 72.5%, the selectivity for cresol was 40.3%, and the selectivity for phenol was 12.6%. The main byproducts were C6-C8 aromatics and C1-4 alkanes. Phenol selectivity represents the excess phenol in the reaction products after excluding the phenol added as an alkyl transfer agent. After 72 hours of continuous operation, the catalyst activity decreased by approximately 50%.
[0055] Example 2
[0056] I. Preparation of Catalyst #2:
[0057] (1) Dissolve 0.005 mol aluminum sulfate, 0.1 mol sodium hydroxide, 0.04 mol hexamethylammonium bromide, and 5 mol deionized water at room temperature. After obtaining a solution, add carbon nanotubes and seed crystals to the solution and stir for 10 min. Then add 1 mol of silica sol and stir until homogeneous to obtain a precursor gel. Aluminum sulfate is calculated as Al2O3, sodium hydroxide as Na2O, and silica sol as SiO2. The weight ratio of carbon nanotubes to silica sol is 1:2, and the weight ratio of seed crystals to silica sol is 1:2. The diameter of the carbon nanotubes is 8-12 nm.
[0058] The precursor gel was placed in a hydrothermal reactor lined with polytetrafluoroethylene and crystallized at 160℃ for 48 h. The product was then filtered, washed, and dried at 100℃ for 6 h to obtain the crystallized product. 10 g of the crystallized product was mixed with 300 mL of 0.5 mol / L NaOH solution and treated with alkali at 80℃ for 60 min. The product was then filtered and washed to obtain ZSM-48 molecular sieve with a silicon-to-aluminum ratio of 100. The ZSM-48 molecular sieve was exchanged in 1.2 mol / L NH4Cl solution (liquid / solid = 8:1) at 80℃ for 1 h, then filtered. The ammonium exchange was repeated three times. The ZSM-48 molecular sieve after ammonium exchange was dried at 100℃ for 20 h and then calcined at 530℃ for 7 h to obtain HZSM-48 molecular sieve. This HZSM-48 molecular sieve is a hierarchical porous molecular sieve with a micro-mesoporous hierarchical channel structure.
[0059] (2) A mixed aqueous solution of phosphoric acid and boric acid was used as the impregnation solution to impregnate the hierarchical porous molecular sieve with an equal volume. 1.2 wt% of phosphorus (P) and 0.8 wt% boron (B) were introduced into the hierarchical porous molecular sieve, with P calculated as P2O5 and B calculated as B2O3. The hierarchical porous molecular sieve with introduced P and B was dried at 100℃ for 5 h and then calcined at 550℃ for 4 h to obtain the modified molecular sieve.
[0060] (3) Using boehmite with an alumina content of 70wt% as a binder, the binder is mixed evenly with the modified molecular sieve, extruded into strips, dried at 100℃ for 5h, and then calcined at 520℃ for 4h to obtain the catalyst support.
[0061] (4) Using a mixed aqueous solution of nickel nitrate and ammonium tungstate, Ni and W elements were loaded onto the catalyst support by an equal volume impregnation method. The catalyst support loaded with Ni and W elements was then dried at 100°C for 5 hours and then calcined at 500°C for 4 hours to obtain catalyst #2.
[0062] In catalyst #2, the mass percentage of binder (alumina) is 20%, the mass percentage of NiO is 2%, and the mass percentage of WO3 is 1%.
[0063] II. Preparation of lower phenols:
[0064] The preparation of cresol in this embodiment is basically the same as in Example 1, except that the catalyst is different. Catalyst No. 2 is used in this embodiment.
[0065] The results showed that the single-pass conversion rate of higher phenols was 52.5%, the total conversion rate was 61.2%, the selectivity for cresol was 45.6%, and the selectivity for phenol was 24.8%. The main byproducts were low-aromatic hydrocarbons and C1-4 alkanes. After 72 hours of continuous operation, the catalyst activity decreased by approximately 38%.
[0066] Example 3
[0067] I. Preparation of Catalyst #3:
[0068] (1) Commercially available HZSM-5 molecular sieve and Hβ molecular sieve were mixed evenly at a mass ratio of 1:1 to form a mixed molecular sieve. Then, a mesoporous insertion technique was used to construct hierarchical channels. The specific steps were as follows: the mixed molecular sieve was immersed in a 1wt% tetrapropylammonium hydroxide (TPAOH) aqueous solution at 80℃ for 12 h, and after washing and drying, a hierarchical channel molecular sieve with a micro-mesoporous hierarchical channel structure was obtained. The mass ratio of tetrapropylammonium hydroxide (TPAOH) aqueous solution to the mixed molecular sieve was 1:1. The total silica-alumina ratio of the mixed molecular sieve was 54, and the silica-alumina ratio of the hierarchical channel molecular sieve was 38.
[0069] (2) Using trimethyl borate as the boron source, the trimethyl borate vaporized at 600℃ is carried into the deposition furnace by nitrogen bubbling at a flow rate of 400 mL / min. The deposition process is carried out for 2 hours to deposit B element on the micro-mesoporous hierarchical channel molecular sieve until the loading of B element reaches 1.5 wt%, thus obtaining the modified molecular sieve.
[0070] (3) Using boehmite with an alumina content of 70wt% as a binder, the binder is mixed evenly with the modified molecular sieve, extruded into strips, dried at 100℃ for 5h, and then calcined at 500℃ for 3h to obtain the catalyst support.
[0071] (4) Using a mixed aqueous solution of nickel nitrate and ammonium heptamolybdate, Ni and Mo elements were loaded onto the catalyst support by an equal volume impregnation method. The catalyst support loaded with Ni and Mo elements was then dried at 100°C for 5 hours and then calcined at 500°C for 4 hours to obtain catalyst #3.
[0072] In catalyst #3, the mass percentage of binder (alumina) is 20%, the mass percentage of NiO is 2%, and the mass percentage of MoO3 is 1%.
[0073] II. Preparation of lower phenols:
[0074] The preparation of cresol in this embodiment is basically the same as in Example 1, except that the catalyst is different. Catalyst No. 3 is used in this embodiment.
[0075] The results showed that the single-pass conversion rate of higher phenols was 68.2%, the total conversion rate was 93.7%, the selectivity for cresol was 70.8%, and the selectivity for phenol was 21.3%. Byproducts included C6-C8 aromatics and a small amount of C9+ heavy aromatics, which were recovered. After 400 hours of continuous operation, the activity of catalyst #3 decreased by about 8%, but the activity recovered well after regeneration.
[0076] Example 4
[0077] I. Preparation of Catalyst #4:
[0078] (1) Commercially available HZSM-5, Hβ, and HMCM-22 molecular sieves were mixed evenly at a mass ratio of 1:1:1 to form a mixed molecular sieve. The mixed molecular sieve was treated with 0.2 mol / L NaOH aqueous solution at 65°C for 2 hours to remove silicon, and then washed with distilled water until neutral to introduce a mesoporous structure, thus obtaining a hierarchical channel molecular sieve with a micro-mesoporous hierarchical pore structure. The total silicon-to-aluminum ratio of the mixed molecular sieve was 75, and the silicon-to-aluminum ratio of the hierarchical channel molecular sieve was 52.
[0079] (2) Using an aqueous solution of phosphoric acid as the impregnation solution, the hierarchical porous molecular sieve was impregnated with an equal volume to introduce 1.5 wt% of phosphorus element into the hierarchical porous molecular sieve, which was calculated as P2O5. The hierarchical porous molecular sieve with added phosphorus element was dried at 100℃ for 5 h and then calcined at 550℃ for 4 h to obtain the modified molecular sieve.
[0080] (3) Using boehmite with an alumina content of 70wt% as a binder, the binder is mixed evenly with the modified molecular sieve, extruded into strips, dried at 100℃ for 5h, and then calcined at 500℃ for 4h to obtain the catalyst support.
[0081] (4) Using a mixed aqueous solution of nickel nitrate and ammonium heptamolybdate, Ni and Mo elements were loaded onto the catalyst support by an equal volume impregnation method. The catalyst support loaded with Ni and Mo elements was then dried at 100°C for 5 hours and then calcined at 500°C for 4 hours to obtain catalyst #4.
[0082] In catalyst #4, the mass percentage of binder (alumina) is 20%, the mass percentage of NiO is 2%, and the mass percentage of MoO3 is 1%.
[0083] II. Preparation of lower phenols:
[0084] The preparation of cresol in this embodiment is basically the same as in Example 1, except that the catalyst is different. Catalyst No. 4 is used in this embodiment.
[0085] The results showed that the single-pass conversion rate of higher phenols was 72.1%, the selectivity of cresol was 76.8%, and the selectivity of phenol was 10.5%. The three molecular sieves were complementary, resulting in high conversion and selectivity levels. After 400 hours of continuous operation, the catalyst activity decreased by approximately 4.6%, but after regeneration, the activity recovered to over 98% of that of the fresh catalyst.
[0086] When phenol as an alkyl transfer agent was removed, the single-pass conversion of higher phenols was 75.1%, the selectivity of cresol was 17.31%, and the selectivity of phenol was 45.3%.
[0087] When phenol, as an alkyl transfer agent, is removed and xylene is added as a raw material, the single-pass conversion rate of higher phenol is 67.1%, the selectivity of cresol is 29.49%, the selectivity of phenol is 8.62%, and the mass ratio of xylene to higher phenol is 1:1.
[0088] This embodiment shows that, compared with the absence of phenol, the addition of phenol slightly decreases the single-pass conversion rate of higher phenols, but significantly improves the cresol selectivity and reduces the phenol selectivity. When xylene is added, compared with the addition of phenol, the single-pass conversion rate of higher phenols, as well as the cresol and phenol selectivity, all decrease to varying degrees, especially the decrease in cresol selectivity is more significant.
[0089] Example 5
[0090] I. Preparation of Catalyst #5:
[0091] HZSM-5, Hβ, and HMCM-22 molecular sieves were prepared separately. During the preparation process, carbon nanotubes were added to the reaction solution as mesoporous agents to form hierarchical molecular sieves with a micro-mesoporous hierarchical pore structure. The prepared HZSM-5, Hβ, and HMCM-22 molecular sieves were then mixed to form a mixed molecular sieve. The preparation methods for each molecular sieve are described in Example 2. The diameter of the carbon nanotubes was 8-12 nm. This mixed molecular sieve is the hierarchical molecular sieve, and the silicon-to-aluminum ratio of the hierarchical molecular sieve is 4:4.
[0092] The mixed molecular sieve was treated using steps (2), (3) and (4) in Example 4 to finally form catalyst #5.
[0093] II. Preparation of lower phenols:
[0094] The preparation of cresol in this embodiment is basically the same as in Example 4, except that the catalyst is different. Catalyst No. 5 is used in this embodiment.
[0095] The results showed that the single-pass conversion rate of higher phenols was 71.5%, the selectivity for cresol was 77.2%, and the selectivity for phenol was 10.8%. When using a mesoporous agent to produce molecular sieves, the mesopores in the molecular sieves were more regular, and the selectivity for cresol was slightly improved compared with Example 4. After continuous operation for 400 hours, the catalyst activity decreased by about 4.3%, and the activity recovered to more than 98% of that of the fresh catalyst after regeneration.
[0096] The selectivity of cresol and phenol in the above embodiments shows that when the catalyst is composed of two molecular sieves, its single-pass conversion rate, total conversion rate, and cresol selectivity of higher phenols are all higher than those of catalysts composed of a single molecular sieve. Furthermore, when the catalyst is composed of three molecular sieves, its single-pass conversion rate, total conversion rate, and cresol selectivity of higher phenols are all higher than those of catalysts composed of two molecular sieves. This indicates that when multiple molecular sieves are used to form a catalyst, the pore size of the channels within the molecular sieves becomes more diverse, which is more conducive to adapting to the complex components with different carbon numbers in alkylphenols produced from coal tar, thereby improving the efficiency of dealkylation and alkyl transfer reactions of alkylphenols, and thus improving the conversion rate of higher phenols and the cresol selectivity.
[0097] Comparative Example 1
[0098] I. Preparation of Catalyst #6:
[0099] Commercially available HZSM-5, Hβ, and HMCM-22 molecular sieves were mixed uniformly in a mass ratio of 1:1:1 to form a mixed molecular sieve. Then, boehmite with an alumina content of 70 wt% was used as a binder. The binder was mixed evenly with the mixed molecular sieve, extruded into strips, dried at 100℃ for 5 hours, and then calcined at 500℃ for 4 hours to obtain the catalyst support. The silica-to-alumina ratio of the mixed molecular sieve was 35.
[0100] Ni and Mo were loaded onto a catalyst support using an equal-volume impregnation method with a mixed aqueous solution of nickel nitrate and ammonium heptamolybdate. The catalyst support loaded with Ni and Mo was then dried at 100°C for 5 hours and subsequently calcined at 500°C for 4 hours to obtain catalyst #6. In catalyst #6, the mass percentage of binder (alumina) was 20%, the mass percentage of NiO was 2%, and the mass percentage of MoO3 was 1%.
[0101] That is, the catalyst #6 in Comparative Example 1 did not undergo mesoporous construction and acid adjustment.
[0102] II. Preparation of lower phenols:
[0103] The preparation of cresol in this embodiment is basically the same as in Example 1, except that the catalyst is different. Catalyst No. 6 is used in this embodiment.
[0104] The results showed that the single-pass conversion rate of higher phenols was 38.5%, the total conversion rate was 62.3%, the selectivity for cresol was 32.1%, and the selectivity for phenol was 18.5%. The amount of olefins and heavy components in the byproducts increased significantly. After 100 hours of operation, the catalyst activity decreased by 25%, and the activity recovery rate after regeneration was only 85%.
[0105] Comparative Example 2
[0106] I. Preparation of Catalyst #7:
[0107] (1) Mix commercially available HZSM-5, Hβ, and HMCM-22 molecular sieves in a mass ratio of 1:1:1 to form a mixed molecular sieve. The silica-alumina ratio of the mixed molecular sieve is 35.
[0108] (2) Using phosphoric acid aqueous solution as impregnation liquid, the mixed molecular sieve was impregnated with an equal volume, and 1.5 wt% of P element was introduced into the mixed molecular sieve, with P element calculated as P2O5. The hierarchical pore molecular sieve with introduced P element was dried at 100℃ for 5 h and then calcined at 550℃ for 4 h to obtain the modified molecular sieve.
[0109] (3) Using boehmite with an alumina content of 70wt% as a binder, the binder is mixed evenly with the modified molecular sieve, extruded into strips, dried at 100℃ for 5h, and then calcined at 500℃ for 4h to obtain the catalyst support.
[0110] (4) Using a mixed aqueous solution of nickel nitrate and ammonium heptamolybdate, Ni and Mo elements were loaded onto the catalyst support by an equal volume impregnation method. The catalyst support loaded with Ni and Mo elements was then dried at 100°C for 5 hours and then calcined at 500°C for 4 hours to obtain catalyst #4.
[0111] In catalyst #7, the binder (alumina) has a mass percentage of 20%, NiO has a mass percentage of 2%, and MoO3 has a mass percentage of 1%. The molecular sieve in catalyst #7 is acid-adjusted using phosphorus but does not undergo mesoporous treatment.
[0112] II. Preparation of lower phenols:
[0113] The preparation of cresol in this embodiment is basically the same as in Example 1, except that the catalyst is different. Catalyst No. 7 is used in this embodiment.
[0114] The results showed that the single-pass conversion rate of higher phenols was 60%, the total conversion rate was 72.3%, the selectivity for cresol was 22.7%, and the selectivity for phenol was 10.5%. The amount of olefins and heavy components in the byproducts increased significantly. After 100 h of operation, the catalyst activity decreased by 30%, and the activity recovery rate after regeneration was only 65%.
[0115] Comparative Example 3
[0116] I. Preparation of Catalyst #8:
[0117] (1) Commercially available HZSM-5, Hβ, and HMCM-22 molecular sieves were mixed evenly at a mass ratio of 1:1:1 to form a mixed molecular sieve. The mixed molecular sieve was treated with 0.2 mol / L NaOH aqueous solution at 65℃ for 2 hours to remove silicon, and then washed with distilled water until neutral to introduce a mesoporous structure, thus obtaining a hierarchical porous molecular sieve with a micro-mesoporous hierarchical pore structure. The silicon-to-aluminum ratio of the hierarchical porous molecular sieve was 38.
[0118] (3) Using boehmite with an alumina content of 70wt% as a binder, the binder is mixed evenly with the layered pore molecular sieve, then extruded into strips, dried at 100℃ for 5h, and then calcined at 500℃ for 4h to obtain the catalyst support.
[0119] (4) Using a mixed aqueous solution of nickel nitrate and ammonium heptamolybdate, Ni and Mo elements were loaded onto the catalyst support by an equal volume impregnation method. The catalyst support loaded with Ni and Mo elements was then dried at 100°C for 5 hours and then calcined at 500°C for 4 hours to obtain catalyst #8.
[0120] In catalyst #8, the binder (alumina) has a mass percentage of 20%, NiO has a mass percentage of 2%, and MoO3 has a mass percentage of 1%. The molecular sieve in catalyst #8 is constructed with mesoporous structure and is not acid-treated.
[0121] II. Preparation of lower phenols:
[0122] The preparation of cresol in this embodiment is basically the same as in Example 1, except that the catalyst is different. Catalyst No. 8 is used in this embodiment.
[0123] The results showed that the single-pass conversion rate of higher phenols was 48.5%, the total conversion rate was 62.3%, the selectivity for cresol was 52.1%, and the selectivity for phenol was 18.7%. The amount of olefins and heavy components in the byproducts increased significantly. After 100 h of operation, the catalyst activity decreased by 45%, and the activity recovery rate after regeneration was only 80%.
[0124] Table 1 shows the volume percentage distribution of micropores, mesopores, and macropores in the total pores of the hierarchical molecular sieves prepared in each embodiment and comparative example.
[0125] Table 1. Pore Size Distribution of Molecular Sieves
[0126]
[0127] The results of the various examples and comparative examples show that the molecular sieves in the catalyst, through the synergistic effect of mesoporous construction, acid center modulation, and metal loading, achieve the dealkylation and alkyl transfer coupling reaction of higher phenols in a fixed-bed reactor, exhibiting advantages such as high conversion rate, good selectivity, and stable operation. Furthermore, the catalyst containing multiple molecular sieves exhibits even better results.
[0128] In addition, Comparative Example 1, using only three molecular sieves to prepare the catalyst, achieved a total conversion rate comparable to that of Example 2, but its selectivity for cresol and phenol was relatively low. Comparative Example 2, although involving acid center modulation, only improved the conversion rate and decreased the selectivity for phenol and cresol. This may be because while acid center modulation increases the catalyst's reactivity, the catalyst's pores prevent the feedstock from passing through quickly, leading to over-reaction and a significant increase in byproducts. Comparative Example 3, using three molecular sieves and also employing mesoporous construction, resulted in higher toluene selectivity than Examples 1 and 2, while its total conversion rate was lower than Example 1 but slightly lower than Example 2, indicating that mesoporous construction effectively improves toluene selectivity. These comparative examples demonstrate that mesoporous construction and acid center modulation need to work in tandem to effectively leverage their advantages and improve the selectivity of the target product.
Claims
1. A method for the directed catalytic conversion of higher phenols into lower phenols, characterized in that, A fixed-bed reactor was used to simultaneously carry out dealkylation and alkyl transfer reactions of high-grade phenols extracted from medium- and low-temperature coal tar in the presence of a catalyst under a hydrogen atmosphere, producing phenol and cresol. After the reaction, the products were separated, and the target product was separated from the unreacted raw material. The unreacted raw material was returned to the reactor for recycling.
2. The method according to claim 1, characterized in that, The raw material also includes an alkyl transfer agent, which is any one of benzene, toluene, and phenol.
3. The method according to claim 1, characterized in that, The reaction conditions were: reaction temperature 300-500℃, reaction pressure 0.1-5.0 MPa, and weight hourly space velocity (WHSV) 0.5-5.0 h⁻¹. -1 The hydrogen-to-oil volume ratio is (200-1000):
1.
4. The method according to claim 1, characterized in that, This catalyst is an acid-metal bifunctional synergistic catalyst, and its preparation method includes the following steps: (1) Using mesoporous insertion technology, a hierarchical pore molecular sieve with a micro-mesoporous hierarchical pore structure was prepared; (2) Modify the hierarchical pore molecular sieve by using P or B elements to obtain modified molecular sieve; (3) The catalyst support is obtained by mixing, bonding, extruding and calcining the modified molecular sieve with a binder; (4) Load an active metal component onto a catalyst support to prepare a catalyst; the active metal component is at least one of Ni, Mo, and W.
5. The method according to claim 4, characterized in that, In step (1), the hierarchical pore molecular sieve is obtained by desiliconizing the molecular sieve through alkali treatment, or by using a mesoporous agent to make the molecular sieve.
6. The method according to claim 5, characterized in that, Mesoporous agents are mesoporous carbon materials, carbon nanotubes, or polymer microspheres with mesoporous structures.
7. The method according to claim 4, characterized in that, The hierarchical porous molecular sieve is any one or a mixture of at least two of Hβ, HZSM-5, HMCM-22, HMOR, HMCM-36 or HZSM-48.
8. The method according to claim 4, characterized in that, In step (2), P or B elements are loaded onto the hierarchical pore molecular sieve by impregnation or chemical vapor deposition. Based on the dry basis mass of the modified molecular sieve, the loading amount of P and B elements on the molecular sieve is 1-5 wt%, where P is calculated as P2O5 and B is calculated as B2O3.
9. The method according to claim 4, characterized in that, The active metal component in the catalyst is 1-20% by mass, calculated as oxide.
10. The method according to claim 4, characterized in that, In step (2), during the modification process, P or B is loaded onto the hierarchical pore molecular sieve using an equal volume impregnation method or an ion exchange method, and then the hierarchical pore molecular sieve is calcined at 500-600℃ for 3-4 hours to form a modified molecular sieve. In step (3), the roasting temperature is 500-560℃ and the roasting time is 3-4h. In step (4), the active metal component is loaded using an equal-volume impregnation method or an ion exchange method. After loading is completed, it is calcined at 500-560℃ for 3-4 hours.
Citation Information
Patent Citations
Method for producing low level phenol from coal tar and lower phenols produced by the method
CN107474864A
A catalyst for the catalytic hydrogenation and demethylation of xylenol, its preparation method and application
CN111068769B